The Effectiveness of Psychomotor Evaluation Using Peer Assessment in the Practicum Activities - Haris Munandar*; Safrina Junita (Universitas Syiah Kuala, 2022)
Practical activity is a series of learning processes related to the assessment of students in the psychomotor domain. A large number of students in a classroom challenged many teachers in conducting skills assessments for students. This study aims to determine the effectiveness of the psychomotor evaluation using peer assessment in the practicum activities. The Method in this research is descriptive quantitative. This research was conducted by adjusting the results of psychomotor evaluation in the practical activities between direct observation and peer assessment. The research was conducted in natural science practicum activities, specifically on plant reproduction material. The study involved 60 college students of the Department of Primary School of Teacher Training Education as the research sample. The effectiveness of psychomotor evaluation using peer assessment techniques can be seen from the suitability of the results of psychomotor evaluation using peer assessment techniques and the results of direct observation. Based on the results of the research, there is a suitable average score of the psychomotor evaluation which is conducted by the peer assessment technique with the average score of the direct observations made by the researcher which is 91.4 and 90.4. The level of suitability of the two average values reached 98.90%. This shows that the implementation of psychomotor evaluation using peer assessment is effective in the practicum activities